Algunos elementos claves para el establecimiento de un proyecto integrado de yuca - Pérez Crespo, C.A. (International Center for Tropical Agriculture, 1991)
Integrated cassava projects are analyzed by depicting topics that project administrators must bear in mind while planning and implementing integrated cassava projects, whose mission is to catalyze a series of institutional interventions with the objective of improving farmer income and generating the socioeconomic development of a region. The need for farmer participation and institutional integration is stressed and the importance of project leadership in drawing together the different actors involved is emphasized. (CIAT)